Passive control methods of Kerala traditional architecture for a comfortable indoor environment: A comparative investigation during winter and summer - A.S. Dili M.A. Naseer Zacharia Varghese (Building and Environment 45 (2010) 1134-1143, 2010)
Kerala is a strip of land on the southwest coast of India lying between Arabian Sea on the west and Western Ghats on the east. The traditional architecture of Kerala is known for its use of natural and passive methods for a comfortable indoor environment. However, it has not been proved by a detailed and quantitative evaluation method so far. A field study was thus conducted in the winter and summer periods to investigate the indoor environmental condition of a typical Kerala traditional residential building. The objective of the investigation was to understand the passive environment control system of Kerala traditional architecture by quantitative analysis of various thermal comfort parameters. It was done by continuously monitoring the indoor and outdoor conditions using a custom made instrument called ``Architectural Evaluation System''. The results show that the natural and passive control system of Kerala traditional architecture provides comfortable indoor environment irrespective of the outdoor climatic conditions